Current-mode Biquadratic Universal Filter Design with Two Terminal Unity Gain Cells - Alpaslan, Halil; Yuce, Erkan (Společnost pro radioelektronické inženýrství, 2012)
A grounded parallel lossy active inductor and two current-mode (CM) universal filters are presented in this paper. All the circuits use two voltage followers (VFs) and a current follower (CF). The parallel lossy active inductor includes a grounded capacitor which is attractive in integrated circuit (IC) technology. The CM universal filters have one input and standard three outputs such as band-pass (BP), low-pass (LP) and high-pass (HP) responses. All-pass and notch outputs can be obtained by adding extra one CF. Suggested structures in this paper can be constructed with commercially available active devices such as AD844s. Non-ideal gain and intrinsic X-terminal parasitic resistor effects are examined. Several computer simulations with SPICE program and experimental results by employing AD844s are drawn to verify theoretical ones.
Keywords: Lossy inductor simulator; current-mode filter; unity gain cell; current follower; voltage follower